KINERJA KARYAWAN DITINJAU DARI EFEKTIVITAS PENERAPAN SISTEM INFORMASI AKUNTANSI, KEAHLIAN PEMAKAI KOMPUTER, DAN KOMPLEKSITAS TUGAS PADA LPD SE-KECAMATAN DENPASAR SELATAN - Ni Nyoman Sri Indah Ratna Gayatri; Komang Krishna Yogantara; Tiara Kusuma Dewi (Journal Research of Accounting, 2022)
The purpose of this study is to determine the effect of the effectiveness of the application of accounting information systems, computer user expertise, and task complexity on employee performance. This research was conducted at LPDs in South Denpasar District. The population in this study were all employees who worked in LPDs in South Denpasar District, amounting to 245 people. The technique used in data collection is by interviewing and distributing questionnaires to LPD employees throughout the South Denpasar District. Sampling using the purposive sampling method with consideration of the criteria used are LPD employees in South Denpasar District who work at least 1 (one) year, do daily work using computers and are directly related to the accounting information system, so that the total sample size is 93 people. This study uses the associative method and the data analysis technique used in this study is the validity and reliability test, the classical assumption test with 3 (three) stages, namely: normality test, heteroscedasticity test, and multicollinearity test. Then, the multiple linear regression analysis was tested, which included: model feasibility test (F test), hypothesis test (t-test), and coefficient of determination test (R2). The results of this study indicate that the effectiveness of the application of accounting information systems has a positive effect on employee performance and computer user expertise has a positive effect on employee performance. While the complexity of the task does not affect employee performance.